2017
DOI: 10.1136/bmjopen-2017-016216
|View full text |Cite
|
Sign up to set email alerts
|

Discontinuation and non-publication of randomised clinical trials supported by the main public funding body in Switzerland: a retrospective cohort study

Abstract: ObjectiveThe Swiss National Science Foundation (SNSF) promotes academic excellence through competitive selection of study proposals and rigorous evaluation of feasibility, but completion status and publication history of SNSF-supported randomised clinical trials (RCTs) remain unclear. The main objectives were to review all healthcare RCTs supported by the SNSF for trial discontinuation and non-publication, to investigate potential risk factors for trial discontinuation due to poor recruitment and non-publicati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
34
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 21 publications
0
34
1
Order By: Relevance
“…1 Among parents who enroll their children and children who assent to enrollment, motivations for participation include research that provides benefit to the child, altruism, and familiarity with the care team and the research personnel. 1 Among parents who enroll their children and children who assent to enrollment, motivations for participation include research that provides benefit to the child, altruism, and familiarity with the care team and the research personnel.…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…1 Among parents who enroll their children and children who assent to enrollment, motivations for participation include research that provides benefit to the child, altruism, and familiarity with the care team and the research personnel. 1 Among parents who enroll their children and children who assent to enrollment, motivations for participation include research that provides benefit to the child, altruism, and familiarity with the care team and the research personnel.…”
mentioning
confidence: 99%
“…4 Enrollment may be particularly difficult in the critical care setting, where parents are likely to be experiencing stress because of their child's condition. 6 The study found that factors related to willingness to enroll their child in research included (1) characteristics of the recruitment-consent encounter, such as timing, location, and information presented; In a prospective cohort study observing 271 consent encounters in pediatric critical care research, Menon et al reported that consent rates were lower for cardiac surgery than other pediatric intensive care encounters and that consent rates were better when the research team was introduced by a member of the patient's care team.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…A Danish group found that 73% of completed trials were published . Among randomized clinical trials supported by the Swiss National Science Foundation, 40% were not published in peer‐reviewed journals, with the number rising to 70% for discontinued randomized clinical trials . And among clinical trials in The Netherlands, trials that were terminated early had a much lower rate of publication, at 33% published, compared with trials that were completed as planned (64% published; adjusted OR 0.2, 95% CI 0.1–0.3) .…”
mentioning
confidence: 99%